Association of longitudinal changes in skeletal muscle mass with prognosis and nutritional intake in acutely hospitalized patients with abdominal trauma: a retrospective observational study - Xi, Fengchan; You, Yong; Ding, Weiwei; Gao, Tao; Cao, Yang; Tan, Shanjun; Yu, Wenkui (Frontiers in Nutrition, 2023)
Background: The objective of this study was to explore whether longitudinal changes in skeletal muscle mass, from hospital admission to 3 weeks post-trauma, are associated with poor prognosis and nutritional intake in acutely hospitalized patients with abdominal trauma. Methods: A single-center retrospective observational review was conducted on 103 patients with abdominal trauma admitted to the Affiliated Jinling Hospital, Medical School of Nanjing University between January 2010 and April 2020. Skeletal muscle mass was assessed by abdominal computed tomography (CT) performed within 14 days before surgery and on post-trauma days 1-3 (week 0), 7-10 (week 1), 14-17 (week 2), and 21-24 (week 3). The skeletal muscle index (SMI) at L3, change in SMI per day (ΔSMI/day), and percent change in SMI per day (ΔSMI/day [%]) were calculated. The receiver-operating characteristic (ROC) curve was used to evaluate the discriminatory performance of ΔSMI/day (%) for mortality. Linear correlation analysis was used to evaluate the associations between ΔSMI/day (%) and daily caloric or protein intake. Results: Among the included patients, there were 91 males and 12 females (mean age ± standard deviation 43.74 ± 15.53 years). Δ SMI4-1/d (%) had a ROC-area under the curve of 0.747 (P = 0.048) and a cut-off value of -0.032 for overall mortality. There were significant positive correlations between ΔSMI4-1/d (%) and daily caloric intake and protein intake (Y = 0.0007501*X - 1.397, R2 = 0.282, R = 0.531, P < 0.001; Y = 0.008183*X - 0.9228, R2 = 0.194, R = 0.440, P < 0.001). Δ SMI/day (%) was positively correlated with daily caloric intake ≥ 80% of resting energy expenditure in weeks 2, 3 and 1-3 post-trauma and with protein intake > 1.2 g/kg/d in weeks 3 and 1-3 post-trauma. Conclusions: Loss of skeletal muscle mass is associated with poor prognosis and nutritional intake in patients admitted to hospital with abdominal trauma.